The Influence Of Fintech On Profit Growth In Umkm In Pangkalpinang City - Christine Christine*; Wendi Wendi; Shella Pratamawati; Nizwan Zukhri (Universitas Syiah Kuala, 2023)
This study aims to test and analyze whether there is a positive and significant influence between fintech variables on profit growth variables in MSMEs in Pangkalpinang City, Bangka Belitung Islands Province. The method that the researchers used in this study was a quantitative method with a quantitative approach that used primary data sources obtained through the distribution of questionnaires with Likert scales. The number of respondents is 100 MSME players in Pangkalpinang City. The sampling method is Nonprobability Sampling with purposive sampling techniques. Data analysis techniques using the help of SPSS software version 25. The results revealed that fintech variables have a positive and significant effect on profit growth in MSMEs in Pangkalpinang City as evidenced by the partial fintech significance value of (t test) of 0.000 0.05 and the calculated t value of 9.835 t table 1.661.